Kedudukan Hadits Sebagai Pedoman Hidup Sekaligus Dasar Penyelenggaraan Pendidikan Islam - Wardah Yuni Kartika; Marsya Al Farin; Amanda Putri Sari; Hafifa Hafifa; Wismanto Wismanto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Islamic education is something that is very urgent in the lives of all mankind. This is because Islamic education is a means by which all humans can achieve their life goals, namely achieving happiness in this world and the hereafter. The foundation of Islamic education which is the most important reference is the hadith. The aim of this research is to reveal the position of hadith in the implementation of Islamic education. The method used in this research is literature study, namely activities carried out by the author related to data collection methods in the bibliography, by reading, taking notes and then managing the necessary information sourced from books, magazines and journal articles related to the theme. So with this method we can reveal the position of hadith as the basis of Islamic education. The results of this research show the position of hadith in Islamic education, namely that it is the main reference in Islamic education. So understanding it requires interpretation. At the same time, hadith provide explanations of concepts in the Qur'an, including education, and serve as examples as guidance.